Comparison between Dexmedetomidine and Midazolam as Sedation During spinal Anesthesia for Cesarean Section - l, Ali Sahi Sachit Agabri; Almarashedy, Mokhaled Mohammed Jaber; Mahmoud, Bahaa Hussein (Open Journal of Physicians and Surgeons, 2026)
Background: Dexmedetomidine is a highly Selective α2-adrenergic agonist. It is an anxiety reducing, sedative, and pain medication. Midazolam is a short-acting benzodiazepine The has anticonvulsant properties in add of the sedation effect. Objectives: To compare the efficacy of dexmedetomidine versus midazolam for sedation during spinal anesthesia in women undergoing cesarean sections Patients and methods: Sixty patients underwent cesarean section under spinal anesthesia and were assigned into 3 equal groups of 20 patients, namely, Dexmedetomidine, Midazolam and controls according to the type of sedation they received. The control group did not receive any sedation and managed according to the standard protocols. Results: Dexmedetomidine showed more sedative intensity than midazolam and controls. the mean Ramsay score was (3.0 ± 0.1), (2.4 ± 0.5) and (1.4 ± 0.5), respectively, (p<0.001). Hemodynamics was mores table in dexmedetomidine than midazolam group; the mean pulse rate in midazolam group was higher than that of each of dexmedetomidine and control groups and systolic blood pressure (SBP) and diastolic blood pressure (DBP) was lower in midazolam group. The systolic, diastolic blood pressure as well as the mean arterial pressure were significantly higher in dexmedetomidine group than that in the other two groups. Conclusions: The Dexmedetomidine is superiors to midazolam as it provides more intense sedation and offers more stable hemodynamics than midazolam in spinal anesthesia for cesarean sections.